2021
DOI: 10.21203/rs.3.rs-725448/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

M2 Macrophages Secrete CXCL13 to Promote Renal Cell Carcinoma Migration, Invasion, and EMT

Abstract: Objective: M2 macrophages are associated with a poor prognosis in a variety of malignancies. There are, however, few relevant investigations in clear cell renal cell carcinoma (ccRCC).Methods: The expression of M2 macrophages in ccRCC tissues was first discovered using immunohistochemistry in this study. Then, M2 macrophages were created in vitro to see how they affected the proliferation, migration, invasion, and EMT of ccRCC cells. Using qPCR and prognostic analysis identifies important chemokine. Antibody n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…M2 macrophages create an environment conducive to tumor survival by releasing growth factors, chemokines, and other inflammatory mediators (Solinas et al, 2009;Lin et al, 2019). In addition, M2 macrophages can also promote tumor metastasis and invasion by promoting angiogenesis and other pathways (Jetten et al, 2014;Xie et al, 2021). To further analyze the differences in composition and function within M2 macrophages, we used bioinformatics to perform an in-depth analysis at the single cell level.…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages create an environment conducive to tumor survival by releasing growth factors, chemokines, and other inflammatory mediators (Solinas et al, 2009;Lin et al, 2019). In addition, M2 macrophages can also promote tumor metastasis and invasion by promoting angiogenesis and other pathways (Jetten et al, 2014;Xie et al, 2021). To further analyze the differences in composition and function within M2 macrophages, we used bioinformatics to perform an in-depth analysis at the single cell level.…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages are essential in the occurrence and development of ccRCC. M2 macrophages can enhance the proliferation, migration, invasion, and EMT of ccRCC cells in an Akt-dependent manner by secreting CXCL13 (Xie et al, 2021). The negative correlation (Table 1) between LAPTM4B and most immune checkpoints partially explained the insensitivity of ccRCC to immunotherapy, this evidence suggested that LAPTM4B may promote the growth and metastasis of renal cancer by boosting the immune escape of tumor cells.…”
Section: Discussionmentioning
confidence: 87%
“…Over the years, M2 macrophages have been reported to exert an immunosuppressive function in multiple cancers [26]. For example, Xie et al [27] demonstrated that M2 macro-phages could secrete chemokine (C-X-C motif) ligand 13 to promote ccRCC migration, invasion, and EMT. Martínez et al [28] showed that overexpression of bone morphogenetic protein 4 could induce polarization of M2 macrophages, thereby facilitating proliferation, invasion, and migration of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%